Slavery in the System of Trans-Saharan Caravans: The Status of Slaves in the Commercial Caravans between the Sudan Region and the Islamic Maghreb during the Medieval Period - Sad, Salim Hadj (Journal of Ecohumanism, 2026)
This study examines the status and experiences of slaves within the trans-Saharan caravan system linking the Islamic Maghreb and the Sudanese regions during the medieval period. It explores the organization and composition of commercial caravans, the routes connecting the Eastern, Central, and Western Maghreb with the Sudan, and the significance of the slave trade as an important component of trans-Saharan commerce. Drawing on medieval Arabic geographical and historical sources, including the works of al-Bakrī, Ibn Hawqal, al-Idrīsī, Ibn Battuta, and Ibn Khaldūn, the study highlights the natural and human challenges encountered by slaves during caravan journeys. It demonstrates that slaves occupied different positions within the caravans, either as guards and laborers or as commodities intended for sale, and that they endured severe hardships arising from the harsh desert environment, scarcity of water, extreme climatic conditions, attacks by bandits, and various forms of physical and psychological exploitation. The study concludes that the trans-Saharan caravan system imposed particularly harsh conditions on slaves, who represented the most vulnerable group within these commercial networks, and whose suffering constituted an integral yet often overlooked aspect of medieval Afro-Maghrebi trade relations.